2018
DOI: 10.1021/acscatal.8b02118
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature C–H Bond Functionalization by Merging Cobalt and Photoredox Catalysis

Abstract: A non-noble metal-free protocol has been developed for C−H bond functionalization at room temperature by merging cobalt-mediated catalysis with photocatalysis. The reaction requires only oxygen as sole oxidant and operated at room temperature under redox-neutral conditions. Visible-light activated photoredox catalyst functions as an electron transfer reagent with oxygen as a terminal oxidant in the cobalt-mediated C−H and N−H bond annulation. The developed methodology allows annulations with various coupling p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(66 citation statements)
references
References 78 publications
0
64
0
2
Order By: Relevance
“…On the other hand, intermolecular competition studies suggested that the electron-rich amide was slightly more favorable, which could be rationalized an electrophilic-type substitution C − H metalation. Based on the mechanistic experiments described above and relevant literature reports [81][82] [77,86]. Thus the Co(III) species could be regenerated, and a strong reductant, Na 2 Eosin Y radical anion (-1.06 V vs SCE) [86] was simultaneously generated.…”
Section: Supporting Informationmentioning
confidence: 96%
“…On the other hand, intermolecular competition studies suggested that the electron-rich amide was slightly more favorable, which could be rationalized an electrophilic-type substitution C − H metalation. Based on the mechanistic experiments described above and relevant literature reports [81][82] [77,86]. Thus the Co(III) species could be regenerated, and a strong reductant, Na 2 Eosin Y radical anion (-1.06 V vs SCE) [86] was simultaneously generated.…”
Section: Supporting Informationmentioning
confidence: 96%
“…To the best of our knowledge, orthoamidation of aldehydes under first row transition metal catalysis has not been realized yet. [18] Our continuous interest in exploring CÀ H bond functionalization using weakly chelating directing groups under base metal catalysis [19] prompted us to develop an efficient and sustainable procedure for the synthesis of 2-aminobenzaldehydes. Towards this goal, herein, we disclose the cobalt-catalyzed ortho-selective C(sp 2 )À H amidation of benzaldehydes with dioxazolones as an easily accessible amidating reagent [11b,20] using Cp*Co(III) as catalyst (Scheme 1).…”
Section: Abstract: Aldehydes; Amidation; Co-catalysis; Transient Dirementioning
confidence: 96%
“…In 2018, Sundararaju and co‐workers also reported a C–H functionalization reaction also using 8‐aminoquinoline as the directing group and Co(acac) 2 as the catalyst (Scheme ) . Compared with the former, the advantage of this reaction was that it did not need stoichiometric Mn(III) as a co‐catalyst.…”
Section: Ortho‐c–h Functionalization Of Aromatic Amidesmentioning
confidence: 99%